Urgensi Pencegahan Siswa Perokok di Lingkungan Sekolah Untuk Mendukung Pencapaian Tujuan SDGs Di Indonesia - Yunarman, Sepri; M. Ilham Gilang,; Sri Wahyu Nurhidayati ,; Arga Dwi Praditya , (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the urgency of controlling smoking behavior among school students in supporting the achievement of the Sustainable Development Goals (SDGs) in Indonesia, especially SDG 3 (Good Health and Well-Being) and SDG 4 (Quality Education). The method used is a literature study by analyzing various studies and survey data in the last ten years related to the prevalence of novice smokers, factors that influence smoking habits, and their impacts on health, economy, and education. The results of the study show that the number of novice smokers in Indonesia has increased, influenced by social, economic, and environmental factors, such as peer influence, cigarette advertising, and lack of strict regulations in the school environment. The impact of smoking on students not only hinders their academic achievement and health, but also increases the economic burden on families and the national health system. Prevention efforts through stricter regulations, health education, and school and family involvement are needed to reduce the number of novice smokers and create a healthy educational environment and support the achievement of SDGs in Indonesia.